Hubungan Promosi Iklan Susu Formula Dengan Pemberian ASI Eksklusif Di Desa Pandanarum Kecamatan Pacet Kabupaten Mojokerto - Fathiya Luthfil Yumni; Cholifah Tri Wahyuni (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
The advertisement promotion of powder milk (formula) affected the giving of exclusive breastfeeding. The amount of exclusive breastfeeding was still underneath. Indonesian health data profileshowed a decline percentage in 2014 related to the amount of infant that got exclusive breastfeedingfrom 0 up to 6 months they are 52.3 %, there are so many factors affected mother to give exclusive breastfeeding (ASI) in Pandanarum village, Pacetsubdistric, Mojokerto. This research used Analytic Correlation design with Cross Sectional Study. The population of this research consisted of mothers who have an infant 0–2 years. The technique in gaining sampling used Cluster Random Sampling.There are 46 mothers who have infant 0-2 years who lived in Pandanarum village. The analysis used was Chi-Square statistical test. The variables consisted of powder milk (formula)advertisementas an independent variable and giving exclusive breastfeeding as a dependent variable. The finding showed that there was significant relationship between advertisement promotion of powder milk (formula) and giving exclusive breastfeeding based on Chi-Square statistical test met (ρ = 0.012 <0.05). The number of outstanding advertisementpromotion of powder milk (formula) hence the need of education for mothers on exclusive breastfeeding promotion and also about the importance of giving exclusive breastfeeding, as well as it benefits such as thrifty, efficient and have a better content compared with powder milk (formula). The promotion is used to attract the public, especially mothers to give exclusive breastfeeding. Keywords: Advertisement Promotion, Exclusive Breastfeeding.